Infusing data literacy in design education: maturing a distributed design observation approach in Portugal - Costa, Nina (2023)
The production of data about design is important to create new knowledge about the discipline and support the development of better public policies. In Portugal, the DesignOBS project is developing these tasks, gathering information about the ecosystem. Databases are very important instruments to understand the discipline to systematically innovate. In this paper, we want to go further and address its literacy. Starting from the assumption that design is an activity of cultural mediation, its role in data interpretation could promote more participatory discussions about the discipline, and ultimately enrich the ecosystem; but data literacy in design is still at its infancy. To address this challenge, the present paper describes a hands-on approach to infuse data literacy in an educational design con- text, to support novice designers navigating a database about design companies. The study adopts a longitudinal case study approach and follows fifteen students from a design master course during the period of one semester. This research is an additional step for the maturation of the process to develop a design observatory in Portugal. It resulted in a set of data-focused infographics about design companies, richer datasets and levered the transformation of the student’s perception of their potential role in the context of data. This study contributes to ongoing discussions at the intersection of data literacy and design, still in an early stage. Moreover, it advances design research by reflecting on the value of adopting designerly approaches to create new materials, diffuse information about the design ecosystem and promote more participatory reflections about the discipline.